A Comprehensive Review Of Potentiometric Biosensors - Singh, Arpit; Singh, Aishwarya; Kumar, Vibha (International Journal of Psychosocial Rehabilitation, 2024)
Potentiometry based on ion-selective electrodes (ISEs) has undergone a renaissance with improvements in the detection limits and selectivities of ISEs, the introduction of new materials, new sensing concepts (from conventional potentiometry to dynamic electrochemistry approaches), and deeper theoretical understanding and modelling of the potentiometric responses of ISEs. The most recent innovations support improvements in software for ion sensing and biosensing. Additionally, adaptable sensing techniques have been created for a wide range of various target molecules, including enzymes, antibodies, aptamers, and peptides, in response to the introduction of new receptors by using ISEs as powerful transducers. Current potentiometric biosensor trends are examined in this paper. Their applications in the biosensing of metal ions, small molecules, DNA, proteins, microorganisms, and poisons have been discussed. This review provides a forecast for potentiometric biosensing based on the integration of potentiometric ISEs with innovative materials and cutting-edge techniques.